Ambiquity and public good provision in large societies - Ralph W. Bailey; Jürgen Eichberger; David Kelsey (University of Heidelberg, Department of Economics, 2004)
In this paper we consider the effect of ambiguity on the private provision of public goods. Equilibrium is shown to exist and be unique. We examine how provision of the public good changes as the size of the population increases. We show that when there is uncertainty there may be less free-riding in large societies.
Keywords: D81; H41; 330; Ambiguity; public goods; Choquet expected utility; Öffentliche Güter; Erwartungsnutzen; Bevölkerung; Trittbrettfahrerverhalten; Theorie; Entscheidung unter Unsicherheit